A Chemoselective Rapid Azo-Coupling Reaction (CRACR) for Unclickable Bioconjugation - Addy, Partha Sarathi; Erickson, Sarah B.; Italia, James S.; Chatterjee, Abhishek (Journal of the American Chemical Society, 2017)
Chemoselective modification of complex biomolecules has become a cornerstone of chemical biology. Despite the exciting developments of the past two decades, the demand for new chemoselective reactions with unique abilities, and those compatible with existing chemistries for concurrent multisite-directed labeling, remains high. Here we show that 5-hydroxyindoles exhibit remarkably high reactivity toward aromatic diazonium ions and this reaction can be used to chemoselectively label proteins. We have previously genetically encoded the noncanonical amino acid 5-hydroxytryptophan in both E. coli and eitkaryotes, enabling efficient site-specific incorporation of S-hydroxyindole into virtually any protein. The S-hydroxytryptophan residue was shown to allow rapid; chemoselective protein modification using the azocoupling reaction, and the utility of this bioconjugation strategy was further illustrated by generating a functional antibody fluorophore conjugate. Although the resulting azo-linkage is otherwise stable, we show that it can be efficiently cleaved upon treatment with dithionite. Our work establishes a unique chemoselective "unclickable" bioconjugation strategy to site-specifically modify proteins expressed in both bacteria and eukaryotes.